Erlebnispädagogik by Werner Michl - Sávai-Átyin, Andrea Regina (Central European Journal of Educational Research, 2022)
Bibliography of the reviewed book: Werner, M. (2020). Erlebnispädagogik. Ernst Reinhardt, GmbH & Co KG Verlag. 3049. ISBN 978-3-8252-5334-9